Development of climate change scenarios for small areasin Vietnam by using the MAGICC/SCENGEN softwarein combination with statistic correction - Hoang, Duc Cuong (VNU, 2014)
Climate change has been happening in scales of the global, regional as well as in Vietnam because of human activities which impulse greenhouse gas increasing in the atmosphere. To cope effectively with climate change, the understanding of future climate based on climate change scenarios, particularly scenarios for small areas, is essential. This paper concerns on the application ofMAGICC/SCENGEN 5. 3 software in combination with statistic correction to develop cli mate change scenarios for small areas in Vietnam. Results showed that the temper ature is increased, while rainfall is changed heterogeneity and seasonally in the regions in Vietnam